2014
DOI: 10.1113/expphysiol.2014.080069
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic chemosensitivity of rostral ventrolateral medullary sympathetic premotor neurons in the in situ arterially perfused preparation of rats

Abstract: New Findings r What is the central question of this study?Brain hypoperfusion is a key factor triggering hypertension through activation of cardiovascular sympathetic vasomotor nerves. However, mechanisms of detecting brain hypoperfusion remain unclear. We hypothesized that the sympathetic premotor neurons in the rostral ventrolateral medulla (RVLM) can sense asphyxia and cause sympathoexcitation. r What is the main finding and its importance?Functionally identified RVLM sympathetic premotor neurons were excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…In rodents, neurons in areas, including the nucleus tractus solitarius and rostral ventrolateral medulla, are directly sensitive to hypoxia and cause sympathoexcitation and augmented BP. 42,43 Moreover, Marina et al 13 showed that hypoxia-induced activation of the rostral ventrolateral medulla in spontaneously hypertensive rats could be supressed by adenosine triphosphate antagonists or a glycogenesis inhibitor. These data indicate that metabolic by-products, which are increased during hypoxemia, can activate the neurons directly controlling sympathetic outflow.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, neurons in areas, including the nucleus tractus solitarius and rostral ventrolateral medulla, are directly sensitive to hypoxia and cause sympathoexcitation and augmented BP. 42,43 Moreover, Marina et al 13 showed that hypoxia-induced activation of the rostral ventrolateral medulla in spontaneously hypertensive rats could be supressed by adenosine triphosphate antagonists or a glycogenesis inhibitor. These data indicate that metabolic by-products, which are increased during hypoxemia, can activate the neurons directly controlling sympathetic outflow.…”
Section: Discussionmentioning
confidence: 99%
“…This region receives convergent input from RTN, from caudal NTS neurons that relay carotid body inputs, from serotonergic neurons and from the C1 adrenergic cells (Bochorishvili et al, 2012; Burke et al, 2014; Song et al, 2011). The C1 neurons are highly responsive to carotid body stimulation and brain hypoxemia (Guyenet, 2014; Koganezawa and Paton, 2014) and arousal from NREM sleep is reliably elicited by C1 cell activation (Burke et al, 2014). …”
Section: Chemoreflexes and Sleepmentioning
confidence: 99%
“…Experimental evidence shows that RVLM neurons have their firing frequency reduced by stimulation of baroreceptor afferent fibres, leading to sympathoinhibitory and hypotensive responses, indicating that the baroreflex activation inhibits the activity of the presympathetic neurons (Haselton & Guyenet, ; Pedrino et al . ; Koganezawa & Paton, ). Therefore, after removal of arterial baroreceptor afferents [sino‐aortic denervation (SAD)], sympathetic overactivity and hypertension are expected in rats (Krieger, ).…”
Section: Introductionmentioning
confidence: 99%
“…The sympathetic tonus regulating the vascular resistance, cardiac output and, consequently, arterial pressure is generated by bulbospinal sympathetic premotor neurons located in the rostral ventrolateral medulla (RVLM; Sun et al 1988;Guyenet, 2006). Experimental evidence shows that RVLM neurons have their firing frequency reduced by stimulation of baroreceptor afferent fibres, leading to sympathoinhibitory and hypotensive responses, indicating that the baroreflex activation inhibits the activity of the presympathetic neurons (Haselton & Guyenet, 1989;Pedrino et al 2013;Koganezawa & Paton, 2014). Therefore, after removal of arterial baroreceptor afferents [sino-aortic denervation (SAD)], sympathetic overactivity and hypertension are expected in rats (Krieger, 1964).…”
Section: Introductionmentioning
confidence: 99%